The Growth Hormone Receptor: Mechanism of Receptor Activation, Cell Signaling, and Physiological Aspects - Dehkhoda, Farhad; Lee, Christine M. M.; Medina, Johan; Brooks, Andrew J. (Frontiers in Endocrinology, 2018)
The growth hormone receptor, although most well-known for regulating growth, has many other important biological functions including regulating metabolism and controlling physiological processes related to the hepato-biliary, cardiovascular, renal, gastrointestinal, and reproductive systems. In addition, growth hormone signalling is an important regulator of ageing and plays a significant role in cancer development. Growth hormone activates the JAK-STAT signalling pathway and recent studies have provided a new understanding of the mechanism of JAK2 activation by growth hormone binding to its receptor. JAK2 activation is required for growth hormone mediated activation of STAT1, STAT3, and STAT5, and the negative regulation of JAK-STAT signalling comprises an important step in the control of this signalling pathway. The growth hormone receptor also activates the Src family kinase signalling pathway independently of JAK2. This review covers the molecular mechanisms of growth hormone receptor activation and signal transduction as well the physiological consequences of growth hormone signalling.